2014
DOI: 10.1109/tim.2014.2323139
|View full text |Cite
|
Sign up to set email alerts
|

Point Cloud-Based Model-Mediated Teleoperation With Dynamic and Perception-Based Model Updating

Abstract: In this paper, we extend the concept of model-mediated teleoperation (MMT) for complex environments and six degrees of freedom interaction using point cloud surface models. In our system, a time-of-flight camera is used to capture a high resolution point cloud model of the object surface. The point cloud model and the physical properties of the object (stiffness and surface friction coefficient) are estimated at the slave side in real-time and transmitted to the master side using the modeling and updating algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Extrapolation is used when the slave device needs to operate outside the area produced by the point-cloud model, although issues are very likely to emerge. The authors of [200] also reported a data reduction of about 90% with guaranteed (significantly high) subjective quality of teleoperation. Augmented feedback information was also considered in [201] again with the use of a stereo camera.…”
Section: F Model-mediated Teleoperation Approachmentioning
confidence: 93%
See 1 more Smart Citation
“…Extrapolation is used when the slave device needs to operate outside the area produced by the point-cloud model, although issues are very likely to emerge. The authors of [200] also reported a data reduction of about 90% with guaranteed (significantly high) subjective quality of teleoperation. Augmented feedback information was also considered in [201] again with the use of a stereo camera.…”
Section: F Model-mediated Teleoperation Approachmentioning
confidence: 93%
“…This combination of perceptual and statistical methods has been made in [199] by first applying the JND threshold and then a double exponential smoothing prediction algorithm to fill in the values not transmitted due to the threshold. Xu et al [200] also applied the perceptual deadband approach to the estimated model parameters to reduce the transmission rate. The proposed framework incorporates 3D sensors to produce a point cloud model of a static rigid object's surface in the remote environment.…”
Section: F Model-mediated Teleoperation Approachmentioning
confidence: 99%
“…In [75], authors proposed a point-cloud-based model mediated (Pcbmm) system for bilateral communication in a transparent and stable way. The system is developed for complex remote environments and these hard environments are modeled using point clouds rather simple geometry approximation.…”
Section: J Sens Actuator Netw 2018 7 X For Peer Review 12 Of 22mentioning
confidence: 99%
“…State-of-the-art solutions that address the aforementioned teleoperation challenges (sensitivity to delay and high packet rate) focus on combining different stability-ensuring control schemes with haptic packet rate reduction methods such as [5], [6].…”
Section: Introductionmentioning
confidence: 99%